Development of Inquiry-Based Chemistry Laboratory Sheet Oriented to Green Chemistry for Improving the Science Process Skills - Putra, Ijtihad Sang; Susilaningsih, Endang; Wardani, Sri (Postgraduate, Universitas Negeri Semarang, Indonesia, 2018)
Science process skills are indispensable for educators in the world of education or in everyday life that includes observing, categorizing, interpreting, forecasting, questioning, formulating hypotheses and communicating. The aim of this research is to develop of inquiry-based chemical practicum green chemistry-oriented for improving the students' science process skills in a colloid material. This research is a type of R & D research with One Group Pretest-posttest Design design applied to test the application of practicum as the product of development. The criteria for the success of this study are valid practicum, increasing KPS and getting a positive response from learners. Research data obtained by observation method, documentation, questionnaire and test. Device validation results obtained valid criteria (3.8 of 4). The results of early practicum KPS were in enough and fewer categories, improved on the final lab in the good and excellent category. The average of cognitive learning outcomes of the broad test classes is 79.20 (> of KKM) and the proportion of classical learning completion is greater than 80% or 24 of the 30 students reach the KKM. Students respond positively to the practicum in the